Applying Structural Equation Modelling for Assessing Factors Influencing Innovation Capacity and Business Efficiency - Nga, Lu Phi; Huy, Nguyen Quoc; Tam, Phan Thanh (Journal of Applied Data Sciences, 2024)
In the context of globalization and competition between businesses in an increasingly fierce international trade environment, participating in production networks and global value chains has become an inevitable requirement for developing each economy, in which business forces play a core and pioneering role. Creativity is critical to achieving significant business success in any business, large or small, in manufacturing, commerce, or service. Implementing innovation and creativity will have a profound and lasting impact on the enterprise's ecosystem. Conversely, companies that fail to innovate risk falling behind and becoming irrelevant in today's rapidly evolving business environment. Therefore, this study aims to analyze the key factors affecting innovation capacity and business efficiency, thereby providing solutions to promote this process. The study applied two methods: qualitative research, conducted through interviews, and focused on ten expert group discussions to adjust the content of observed variables to suit the characteristics of the business. Quantitative research was undertaken in 700 samples of representative managers representing 700 small and medium enterprises to test the model and research hypotheses. The findings show five factors affecting innovation capacity, with a significance of five percent, and innovation capacity affecting business efficiency. This result contributes to academic value and is a reference for research on innovation capacity in Vietnam in the coming years. There are five policy implications and contributions to promoting and building a creative culture in businesses, stimulating creativity and passion. After all, developing an innovative culture in businesses will create the role of individuals and groups with endless intelligence and creative passion for creating unique, different, and valuable products with high added value, significantly contributing to promoting growth in businesses.